A Note on Feasibility and Optimality of Transportation Problem - Adhikari, Purnima; Thapa, Gyan Bahadur (Journal of the Institute of Engineering, 2014)
Transportation problem is one of the predominant areas of operations research, widely used as a decision making tool in engineering, business management and many other fields. In this paper, we present a brief literature review of transportation problem with its mathematical models in balanced and unbalanced cases. We report the basic feasible solution and hence the methods to attain optimal solution of the balanced transportation problem. Finally, we describe the primal-dual case of the problem with counter examples. DOI: http://dx.doi.org/10.3126/jie.v10i1.10879 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014, pp. 59–68